Meningkatkan Literasi Dan Inklusi Keuangan Digital Melalui Pemahaman Dasar Tentang Fintech Bagi Keluarga Penerima Manfaat PKH - Nurhayati Lubis; Nurhayanti; M. Wahyu Pratama Putra; Liza Ulfiana (Hikamatzu | Journal of Multidisciplinary, 2026)
The advancement of digital financial technology has transformed the distribution of social assistance programs, including the Family Hope Program (Program Keluarga Harapan/PKH), which increasingly relies on digital financial services. This shift requires PKH beneficiaries to have adequate digital financial literacy and a basic understanding of financial technology (fintech) to independently and securely access and manage assistance funds. However, limited digital financial literacy among beneficiaries remains a significant challenge, potentially hindering program effectiveness and increasing the risk of transaction errors and digital fraud. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance digital financial literacy and inclusion by providing fundamental fintech education to PKH beneficiaries. The program employed a participatory and educational approach through stages of preparation, education and socialization, mentoring, and evaluation. Activities were conducted in selected villages and urban areas involving PKH facilitators and local government partners. The results demonstrate improved participants’ understanding of basic fintech concepts, utilization of digital financial services, and awareness of transaction security and personal data protection. This program is expected to support sustainable financial inclusion and promote greater independence among PKH beneficiaries in managing social assistance funds effectively and responsibly.